The impact of intraoperative Fogarty balloon dilation on arteriovenous fistula success: clinical and functional outcomes - Ersoy, Güler G; Tamtekin, Burak; Taskent, İsmail (Edizioni Minerva Medica, 2025)
An effectively functioning arteriovenous fistula (AVF) is vital for end-stage renal disease patients. This study aims to evaluate the effects of Fogarty® balloon catheter dilation on creating an effectively functioning AVF.This retrospective cohort study was conducted at our clinic between 2020 and 2022. A total of 120 patients underwent arteriovenous fistula (AVF) creation with intraoperative Fogarty® balloon catheter dilation. Inclusion criteria required the presence of a palpable radial artery and superficial vein in the non-dominant arm, which was confirmed via Doppler ultrasound when necessary. The surgical approach involved side-to-side anastomosis between the radial artery and cephalic vein, followed by intraoperative dilation of the artery, vein, and anastomotic area using a Fogarty® balloon catheter after completion of the anastomosis.The study included 120 patients aged between 26 and 89 years, with a nearly equal gender distribution (57 females, 47.5%; and 63 males, 52.5%). The success rate of arteriovenous fistulas (AVFs) was evaluated according to the number of patients who were able to start adequate hemodialysis 6 weeks after surgery. At 6-week follow-up, 114 patients successfully started hemodialysis through these AVFs. In contrast, six patients could not obtain an adequate AVF for effective hemodialysis. As a result, the overall success rate was calculated as 95%.This study suggests that intraoperative Fogarty balloon dilatation may contribute positively to the success rate of AVF creation. The findings indicate that this technique could be considered as a potential intraoperative strategy to optimize AVF outcomes, especially in patients with challenging vascular anatomy or a history of AVF failure.
Keywords: Male; Adult; Aged, 80 and over; Middle Aged; Dilatation; Arteriovenous Shunt, Surgical; Treatment Outcome; Renal Dialysis; Radial Artery; Humans; Kidney Failure, Chronic; Female; Vascular Patency; Retrospective Studies; Aged